Poster 157: Total Intravenous Anesthesia (TIVA) Compared to Traditional General Anesthesia in Shoulder Arthroscopy in the Beach Chair Position. Issue 7 (30th July 2022) - Sharareh, Behnam; Tamma, Poornima; Shah, Anup; Barrera, Lindsay
Objectives: Shoulder arthroscopy is commonly performed in the beach chair position, which has been linked to cerebral oxygen desaturation. Previous studies comparing general anesthesia to total intravenous anesthesia (TIVA) using propofol indicate that TIVA can preserve cerebral perfusion and autoregulation, as well as shorten recovery time and reduce the incidence of postoperative nausea and vomiting. However, few studies have evaluated the use of TIVA in shoulder arthroscopy. Thus, this study seeks to determine if TIVA is superior to traditional general anesthesia methods in terms of improving operating room efficiency, shortening recovery time, and reducing adverse events while theoretically preserving cerebral autoregulation in patients undergoing shoulder arthroscopy in the beach chair position. Methods: This is a retrospective study of patients undergoing shoulder arthroscopy in the beach chair position, comparing two anesthetic techniques. 150 patients were included (75 TIVA and 75 general anesthesia). Unpaired t-tests were used to determine statistical significance. Outcome measures included operating room times, recovery times, and adverse events. Results: Compared to general anesthesia, TIVA significantly improved total recovery time (120.3 ± 31.0 min compared to 131.5 ± 36.8 min; p = 0.048). TIVA also decreased time from case finish to out-of-room (6.5 ± 3.5 min compared to 8.4 ± 6.3 min; p = 0.021). However, the in-room to case start time was slightly longer for the TIVA group (31.8 ± 7.22 min compared to 29.2 ± 4.92 min; p = 0.012). There were fewer readmissions in the TIVA group compared to the general anesthesia group (p = 0.08), and TIVA had lower rates of postoperative nausea and vomiting (p = 0.22), and higher intraoperative MAPs (87.1 ± 11.4 mmHg in the TIVA group, compared to 85.0 ± 9.3 mmHg in the general anesthesia group; p = 0.22). Conclusions: TIVA may be a safe and efficient alternative to general anesthesia in shoulder arthroscopy in the beach chair position. Larger scale studies are needed to evaluate the risk of adverse events related to impaired cerebral autoregulation in the beach chair position. Table 1. Demographics Table 2. Operating Room and Recovery Times Table 3. Adverse Events